Effect of Water Seed Priming on Establishment of Direct Seeded Rice in Well Watered Conditions and Aerenchyma Formation under Varying Water Regimes - Quaqua Mulbah; Joseph Adjetey (AGRIVITA, Journal of Agricultural Science, 2018)
The application of seed hydro-priming as a tool for managing the adverse effect of flooding on seed germination and emergence in rice was studied, along with aerenchyma formation in sections of roots for comparisons between rice subjected to flooded and non-flooded conditions during establishment. Three replicates of three hydro-priming times (0, 24 and 48 h) were used on three cultivars. Seeds were germinated in a growth chamber at 25 o C, 65 % RH, or sown in pots in a controlled temperature glasshouse for the emergence and aerenchyma studies. Aerenchyma formation in root cortical tissues was determined from microscopic images of hand-cut sections at 5 and 50 mm behind the tips of 60-70 mm long nodal roots. The results showed that hydro-priming for both 24 and 48 h significantly hastened germination and emergence. Water seed-priming increased plant height from 20 mm to 40 mm 4 days after sowing. Flooding for 7 days significantly enhanced aerenchyma formation at 50 mm behind the root tips. The results showed that hydropriming for 48 h was the best seed invigoration treatment for shortening the mean emergence time. It hopefully provides seeds an opportunity to escape from the negative effect of flooding on seedling establishment.